Development of selected coagulation factors and anticoagulants in preterm infants by the age of six months - Salonvaara, Marjut; Riikonen, Pekka; Vahtera, Elina; Mahlamäki, Eija; Heinonen, Kirsti; Kekomäki, Riitta (Thrombosis and Haemostasis, 2004)
The development of the coagulation and anticoagulation system in preterm infants was assessed, with special emphasis on extremely low birth weight (ELBW) infants and haemorrhagic or other complications after birth. Coagulation factors II (prothrombin),V (FV),VII (FVII) and X (FX) were analysed at birth and at a corrected age of six months. In addition, antithrombin (AT), protein C (PC) and protein S (PS) were measured at six months, and DNA samples were tested for Factor V Leiden (R506Q). Eighty-two infants, with a median gestational age (GA) of 32 weeks (range 24–36) and a median birth weight of 1562 g (range 695–3520), were studied. Fifteen of these were ELBW infants (range 695-1000g). Prothrombin, FV, FVII and FX reached healthy term six-month-old infant activity levels. Prothrombin and FX did not reach adult values; median activity levels remained at 82% and 78%, respectively. During the follow up, the FV and FVII levels of the ELBW infants (GA 24-27 weeks) increased more than those of the preterm infants born with higher GA (p < 0.001). At birth, prothrombin correlated significantly with FV, FVII and FX (p < 0.001). FVII at birth and at six months correlated significantly with PC (p= 0.021 and p= 0.009, respectively). These findings indicate that the gain in the coagulation factor concentrations in infancy is greatest in infants with the lowest GA at birth. Interesting new inter-relations of coagulation factor and physiological anticoagulant levels may indicate that there are still unrecognised pathways in the function of newborn haemostasis.
Keywords: Prematurity; infant; coagulation factor; physiological anticoagulant; development